Students’ Views On Using Collaborative Strategic Reading (CSR) To Develop Arabic Composition Writing Skills - Azman, Yusra; Bin Chik, Abdul Rahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Previous studies have indicated decreased students' proficiency in Arabic composition writing. A survey showed that 63.4% of students received a